2019
DOI: 10.1108/jpbm-09-2018-2014
|View full text |Cite
|
Sign up to set email alerts
|

Message content features and social media engagement: evidence from the media industry

Abstract: Purpose This paper aims to uncover the drivers of consumer-brand engagement on Facebook, understood here as users’ behavioral responses in the form of clicks, likes, shares and comments. We highlight which content components, interactivity cues (calls to action [CTA]) and media richness (e.g. video, photo and text) are most effective at inducing consumers to exhibit clicking, liking, commenting and sharing behaviors toward branded content. Design/methodology/approach This study analyzes 757 Facebook-based br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 49 publications
3
85
0
1
Order By: Relevance
“…Given the limited research on contributing intentions (like, comment, share) to different types of brand-related content on social media, the present analysis contributes to a greater understanding of what stimulates social media users to contribute to brand-related activities. Additionally, this research study contributes to the growing body of research that focuses on the brand-related content type on social media (Karpinska-Krakowiak and Modlinski, 2018, Vargo, 2016, Moran et al, 2019 by analyzing the content from different perspectives, to be precise, by analyzing lifestyle, commercial messages and personal opinions, following the perspective used by Fu et al (2017). The results of this study enriches the previous literature by highlighting the significant influence of communal incentives on intentions to contribute to brand-related content on social media.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Given the limited research on contributing intentions (like, comment, share) to different types of brand-related content on social media, the present analysis contributes to a greater understanding of what stimulates social media users to contribute to brand-related activities. Additionally, this research study contributes to the growing body of research that focuses on the brand-related content type on social media (Karpinska-Krakowiak and Modlinski, 2018, Vargo, 2016, Moran et al, 2019 by analyzing the content from different perspectives, to be precise, by analyzing lifestyle, commercial messages and personal opinions, following the perspective used by Fu et al (2017). The results of this study enriches the previous literature by highlighting the significant influence of communal incentives on intentions to contribute to brand-related content on social media.…”
Section: Discussionmentioning
confidence: 90%
“…Vargo (2016) empirically proved that content type of brand-related posts has a significant effect on number of retweets and likes, while de Vries et al (2012) suggested that the content of brand post is one of the factors driving brand post popularity. Moreover, the research studies of Cvijikj and Michahelles (2013), Karpinska-Krakowiak and Modlinski (2020), Moran et al (2019), Luarn et al (2015) indicated that content type of brand posts is a significant factor for all measures of engagement (liking, commenting and sharing) on social media, applying diverse classifications of content type. Similarly, Fu et al (2017) stated that share intentions of social media users are subject to content type.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, Antoniadis et al (2019) attempt to explore new ways of analysing the social interactions by including analysis of the Facebook 'reaction buttons'. A complementary perspective on consumer interactions analysed by the public social media metrics offer studies employing industry data (Gavilanes et al, 2018;Lee et al, 2018;Moran et al, 2019). In these studies, additional behavioural features, such as clicks and click-throughs, are considered as a measure of attention given to a post.…”
Section: Antecedents Of Cementioning
confidence: 99%
“…The studies explore relationships between various post types (Vargo, 2016), post characteristics, such as vividness, interactivity (Schultz, 2017) or content characteristic, such as brand personality (Lee et al, 2018) and behavioural interactions as captured by the social media metrics including likes, comments and shares. In comparison to studies that take a single post as a unit of analysis, Tafesse (2016) A complementary perspective on consumer interactions analysed by the public social media metrics offer studies employing industry data (Gavilanes et al, 2018;Lee et al, 2018;Moran et al, 2019). In these studies, additional behavioural features, such as clicks and click-throughs, are considered as a measure of attention given to a post.…”
Section: Content Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation